Paket Pendidikan Kesehatan Peduli Reproduksi (P2KPR) Terhadap Pengetahuan dan Sikap Remaja Terhadap Pernikahan Dini - Nur Uliasari, Silvia; Yulianti Wuriningsih, Apriliani; Distinarista, Hernandia (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Child marriage violates children's rights. This research analyzes the impact of reproductive health education on adolescents' awareness and perspectives about early marriage. It also evaluates adolescent characteristics, including factors like age and level of education, parental income, and culture, and compares teenagers' knowledge and attitudes regarding early marriage both prior to and following receiving reproductive health education.This the study employed a quantitative design with quasi-experimental methods in the intervention group. Data collection includes a non-probability sampling technique using two questionnaires: a knowledge questionnaire on reproductive health related to child marriage and a survey assessing teenagers' perspectives on early marriage. The research includes a pretest and posttest. The Shapiro-Wilk test for normality indicated that the data followed a normal distribution with a p-value of 0.05. The Paired T-Test yielded a p-value of 0.000 (< 0.05), demonstrating a significant change in teenagers' knowledge and attitudes before and after receiving health education. These findings suggest that reproductive health education has a positive impact on teenagers' knowledge and attitudes toward early marriage at MA N 2 Rembang.